2017
DOI: 10.1080/09638288.2017.1292320
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of health-related quality of life after stroke: results from a one-year prospective cohort study

Abstract: The present study identified four distinct trajectories of physical and psychosocial HRQoL. The findings indicate that psychological factors are the most important factors in identifying stroke patients at risk of unfavorable HRQoL trajectories. Using these factors will help to identify vulnerable patients and guide rehabilitation in the early stages post stroke. Implications for rehabilitation Clinicians should be aware that health-related quality of life follows distinct trajectories stable high, stable low,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 47 publications
4
72
1
9
Order By: Relevance
“…Despite the global advancement in stroke treatment and care, recent literature has reported that 40–60% of stroke survivors experience moderate‐to‐severe disabilities that require rehabilitative or long term care (Van Mierlo, van Heugten, Post, Hoekstra, & Visser‐Meily, ). As a result, stroke survivors rely heavily on their families for ongoing care, recovery, and even palliative care over long periods (Costa, Costa, Martins, Fernandes, & Brito, ; Hayashi, Hai, & Tai, ; Kable, Pond, Baker, Turner, & Levi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the global advancement in stroke treatment and care, recent literature has reported that 40–60% of stroke survivors experience moderate‐to‐severe disabilities that require rehabilitative or long term care (Van Mierlo, van Heugten, Post, Hoekstra, & Visser‐Meily, ). As a result, stroke survivors rely heavily on their families for ongoing care, recovery, and even palliative care over long periods (Costa, Costa, Martins, Fernandes, & Brito, ; Hayashi, Hai, & Tai, ; Kable, Pond, Baker, Turner, & Levi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In stroke, specifically, previous research has revealed associations between psychological factors and participation or quality of life (3)(4)(5). Research has shown that proactive coping, self-efficacy, extraversion and optimism are related to better outcomes, whereas passive coping, neuroticism and pessimism are related to worse outcomes (3)(4)(5)(6)(7). These strong associations with outcome highlight the importance of gaining knowledge about the properties of these psychological factors, such as their stability after stroke.…”
mentioning
confidence: 99%
“…The aim of the present study is to provide an overview of the current research, examining the role of personality variables in recovery of stroke survivors. There is growing evidence that personality plays an important role in recovery in patients after stroke (van Mierlo et al, 2017). The review aims to identify the variety of research objectives and most promising issues in current psychological research of the personality in stroke patients and its influence on recovery.…”
Section: The Present Studymentioning
confidence: 99%
“…The recovery or survival of patients is defined mostly as well-being or quality of life (Robinson-Smith, Johnston, & Allen 2000;Afanasiev, Aharon-Peretz, & Granot, 2013;Morris et al, 2013;Teoh et al, 2009;Donnellan et al, 2010;Tielemans et al, 2015;Lapadatu & Moris, 2017;van Mierlo et al, 2017) or physical independence (Hama et al ,2007;Robinson-Smith, Johnston, & Allen, 2000;Gainotti et al, 2001).…”
Section: Outcome Variables and Their Predictorsmentioning
confidence: 99%
See 1 more Smart Citation